The “spillover effect” of algorithmic management and how (not) to tame it - Aloisi, Antonio; Potocka Sionek, Nastazja (Edward Elgar Publishing, 2024)
This chapter delves into the implications of the algorithmic management (AM) “spillover effect”, namely the diffusion of AM systems and practices from the platform economy to conventional work settings and the broader labour market. The AM spillover is tracked across the factual, jurisprudential and legislative dimensions. The crucial questions on which this chapter is targeted are as follows. Are the existing judicial and regulatory responses keeping pace with developments? What are the lessons to be learned from the first wave of litigation concerning AM in the food delivery sector and the first generation of laws targeting AM in the platform economy? Finally, what is the way forward when it comes to addressing the AM spillover most effectively? This chapter begins by dissecting the tools and practices adopted to engage, dispatch, manage, control and assess people who perform platform work. It then examines the case law and regulatory instruments addressing AM in the platform economy and beyond at both EU and national levels. The analysis reveals a significant shift in focus towards data protection, non-discrimination, and working conditions for larger workforce segments. Moreover, a normative critique of the emerging fragmented regulatory approach is presented, contending that a comprehensive solution requires the effective implementation of the existing legal framework and the design of AM specific legislation to close the gaps in the EU and national acquis.
Keywords: Algorithmic management; Platform work; AI Act; Case law; Transparency; Data protection; 56 Ciencias Jurídicas y Derecho; ODS 8 - Trabajo decente y crecimiento económico